Nectar and Pollen Productivity of Common Chicory - Adamchuk, Leonora; Bilotserkivets, Tetiana; Šimková, Jana (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
There is a need for further study of new and forgotten species of high-yielding plants for the expansion of biodiversity of the forage base of honey bees and the receipt of high-quality commercial products at bee-farms. The aim of research was to explore pollen and honey properties of common chicory (Cichorium intybus L.). The selection of plant samples was carried out in Kyiv, Vinnytsia, Khmelnytsky, Poltava, Sumy, Chernihiv and Kirovohrad regions of Ukraine. Standard statistic and morphometric methods, as well as mathematical formulas were used for determining the biological performance indicators. A long flowering period of common chicory was ascertained in the range from 75 to 102 days. Plant productivity indicators for honey bees were established. Biological nectar productivity was in the range from 92.55 to 190.04 g from one common chicory plant. Honey productivity was in the range from 166.59 to 301.34 kg/ha. The biological pollen productivity of one plant of common chicory was in the range from 1.785 to 3.064 g. As a result of pollen analysis of polyfloral honey obtained during the summer of 2016 the pollen grains of common chicory were found in the range from 1 to 27%. Pollen lumps of common chicory in the range from 10 to 80% of the total fee were in polyfloral bee pollen collected during the summer of 2016. The morphometric parameters of the bee pollen were ascertained: the sharping level of the pollen lump was 4 ±0.15 points, the weight of one pollen lump was 7.21 ±0.255 mg, the length of one pollen lump was 3.42 ±0.048 mm, the width of one pollen lump was 2.97 ±0.070 mm. Our further research in this direction may be conducted to determinate of the biologically active components of cichorium honey and bee pollen.